Winter Limnology: How do Hydrodynamics and Biogeochemistry Shape Ecosystems Under Ice?. Issue 6 (11th June 2021) - Jansen, Joachim; MacIntyre, Sally; Barrett, David C.; Chin, Yu‐Ping; Cortés, Alicia; Forrest, Alexander L.; Hrycik, Allison R.; Martin, Rosemary; McMeans, Bailey C.; Rautio, Milla; Schwefel, Robert
Abstract: The ice‐cover period in lakes is increasingly recognized for its distinct combination of physical and biological phenomena and ecological relevance. Knowledge gaps exist where research areas of hydrodynamics, biogeochemistry and biology intersect. For example, density‐driven circulation under ice coincides with an expansion of the anoxic zone, but abiotic and biotic controls on oxygen depletion have not been disentangled, and while heterotrophic microorganisms and migrating phytoplankton often thrive at the oxycline, the extent to which physical processes induce fluxes of heat and substrates that support under‐ice food webs is uncertain. Similarly, increased irradiance in spring can promote growth of motile phytoplankton or, if radiatively driven convection occurs, more nutritious diatoms, but links between functional trait selection, trophic transfer to zooplankton and fish, and the prevalence of microbial versus classical food webs in seasonally ice‐covered lakes remain unclear. Under‐ice processes cascade into and from the ice‐free season, and are relevant to annual cycling of energy and carbon through aquatic food webs. Understanding the coupling between state transitions and the reorganization of trophic hierarchies is essential for predicting complex ecosystem responses to climate change. In this interdisciplinary review we describe existing knowledge of physical processes in lakes in winter and the parallel developments in under‐ice biogeochemistry and ecology. We then illustrate interactions between these processes, identify extant knowledge gaps and present (novel) methods to address outstanding questions. Plain Language Summary: Winter is an important but poorly understood period for lake ecosystems at high latitudes. Incoming solar radiation is diminished by ice and (often) snow, flows of oxygen and substrates such as organic matter or nutrients from outside the lake are limited, and wind no longer causes turbulent mixing of the water column. The sediments become a source of heat as well as of solutes which drive denser water toward the bottom. The resulting density stratification creates a template for the development of winter ecosystems. Distinct oxygenated and oxygen‐depleted zones will affect microbial community structure and the habitat and behavior of zooplankton and fish. Conditions can rapidly change in spring with increased irradiance and incoming snowmelt. This paper reviews how physical, biogeochemical and biological processes act together to shape aquatic ecosystems in winter and in spring. In addition, we present an overview of the unknowns regarding the interactions between the different processes, which can now be posed due to improved understanding of under‐ice hydrodynamics and the nature of lake ice, of biogeochemistry, and of ecology. However, work to date has largely been conducted within distinct disciplines. We therefore outline interdisciplinary approaches that can bridge current knowledge gaps in winter limnology. Key Points: Ecosystems of seasonally ice‐covered lakes are governed by poorly understood interactions between abiotic and biotic processes Density‐driven currents enable gradients in redox potential, create niche habitats and redistribute substrates and organisms under ice Winter limnology has tended to progress within disciplines; an interdisciplinary approach is necessary to resolve extant knowledge gaps